Assess the Impact of a Project-Based Learning Approach on the Development of 21st Century Skills - Rocha, Thiago; Mendes, Clara; Wardhani, Wahju Dyah Laksmi (Yayasan Pedidikan Islam Daarut Thufulah, 2025)
The increasing demand for adaptable, collaborative, and innovative professionals has positioned 21st century skills—such as critical thinking, creativity, communication, and collaboration—at the center of educational priorities worldwide. Traditional instruction often fails to cultivate these competencies, prompting the need for more experiential, student-centered learning models. Project-Based Learning (PBL), with its emphasis on real-world problem-solving and interdisciplinary inquiry, has emerged as a promising pedagogical approach to support the development of these essential skills. This study aims to assess the impact of PBL on secondary students’ acquisition of key 21st century skills. Using a quasi-experimental design, the research involved 160 students divided into experimental (PBL) and control (conventional instruction) groups. Over ten weeks, the experimental group engaged in structured project cycles aligned with curriculum standards, while the control group followed traditional content delivery. Pre- and post-intervention assessments, student reflections, and teacher evaluations were analyzed to measure skill development. Results revealed that students in the PBL group showed statistically significant improvements in collaboration, problem-solving, and creative thinking compared to the control group. Teachers also reported increased learner autonomy and engagement. The study concludes that PBL is a viable strategy for fostering 21st century competencies in contemporary classrooms.